Focused or Comprehensive Written Corrective Feedback: Exploring Students’ Preferences for Written Corrective Feedback - Arshad Iqbal; Dr. Hussain Ahmad (Al-Qanṭara, 2023)
Although researchers have theorized that focused written corrective feedback may be more conducive to noticing and internalization on account of the fact that learners have limited processing capacity and should not, therefore, be burdened with attending to feedback on multiple errors at the same time (Ellis et al., 2008; Frear & Chiu, 2015), several qualitative studies have reported that learners prefer comprehensive written corrective feedback targeting all their errors (Lee, 2005; Amrhein & Nassaji, 2010; McMartin-Miller, 2014). As most studies investigating the relative effectiveness of the two types of feedback focus have not produced any conclusive evidence (Ellis et al., 2008; Sheen et al., 2009; Frear& Chiu, 2015; Rahimi, 2019), it is worth investigating if students' preference for comprehensive written corrective feedback is ubiquitous, well-founded and in line with the findings from the empirical research. This paper reports a qualitative research that explored four EFL students' relative preferences of focused- and comprehensive written corrective feedback using semi-structured interviews and analyzed the data employing thematic analysis. The results revealed that the students showed a clear-cut preference for comprehensive feedback. However, since research in the domain of feedback focus is largely inconclusive, students' preferences might not be well-informed by the research in the field, as they were found to assess feedback based on its quantity rather than quality. They seemed to be guided by the fact that more is better. Teachers, therefore, need to strike a balance between their students' preferences for feedback focus and the findings from research. The study recommends that teachers provide WCF in a non-polar manner adapting it to their students' needs and writing proficiency rather than solely founding their feedback decisions on the basis of their students' priorities.